2013
DOI: 10.1002/phar.1280
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Excessive Anticoagulation Among Hospitalized Adults Receiving Warfarin Therapy Using a Pharmacist‐Managed Dosing Protocol

Abstract: Even in a highly standardized system for warfarin dosing by a pharmacist-managed protocol, higher disease severity and poor nutritional status placed hospitalized patients at greater risk of experiencing excessive anticoagulation. In addition, administration of interacting drugs that highly potentiate warfarin's effect or the occurrence of diarrheal illness may predict increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…In 2012, the first study using a detailed dosing schedule for both the initiation and continuation of warfarin was published . That study and many other published literatures may be ideal references for detailed dosing recommendations and pharmaceutical care detailed.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, the first study using a detailed dosing schedule for both the initiation and continuation of warfarin was published . That study and many other published literatures may be ideal references for detailed dosing recommendations and pharmaceutical care detailed.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol underwent multiple revisions to arrive at the current version; this was published in 2013. 13 Given the primary aim of the project, our team prospectively monitored the performance of the protocol, analysing the cases in which patients on the protocol had an INR >5 to identify potential reasons for these defects. This information was then used in new iterations of the protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Daily INR values were measured while on the protocol. 13 Warfarin dosing and the pharmacists’ notes are available to all providers in the electronic medical record.…”
Section: Methodsmentioning
confidence: 99%
“…Because HPAs can cause dangerously high INRs (>4.5) within two to six days of initiation, it is possible that many of these unmonitored patients had a clinically notable bleeding risk that was unknown to their providers. 3,12,24 FMEA identified over 130 specific failure modes potentially contributing to these adverse events (INR of >4.5 and bleeding events). This study was unique because it not only showed the possible consequences of administering warfarin with HPAs but also semiquantitatively established how to best intervene on the basis of a systematic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Trimethoprimsulfamethoxazole, metronidazole, fluconazole, voriconazole, and miconazole are considered HPAs because they inhibit CYP metabolism. [12][13][14] The interaction between warfarin and HPAs results in appreciably increased INRs and is frequently missed by outpatient warfarin monitoring programs. 11,[15][16][17][18] For example, the addition of trimethoprimsulfamethoxazole to warfarin therapy resulted in INR increases of ≥2 in more than one third of patients.…”
mentioning
confidence: 99%